2018
DOI: 10.1177/2048872618813846
|View full text |Cite
|
Sign up to set email alerts
|

Pre-hospital risk assessment in suspected non-ST-elevation acute coronary syndrome: A prospective observational study

Abstract: Background: Pre-hospital risk stratification of non-ST-elevation acute coronary syndrome (NSTE-ACS) by the complete HEART score has not yet been assessed. We investigated whether pre-hospital risk stratification of patients with suspected NSTE-ACS using the HEART score is accurate in predicting major adverse cardiac events (MACE). Methods: This is a prospective observational study, including 700 patients with suspected NSTE-ACS. Risk stratification was performed by ambulance paramedics, using the HEART score; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 33 publications
0
43
0
2
Order By: Relevance
“…Recent studies have shown the safety of identifying low-risk chest pain patients in a prehospital environment 22 23. The FAMOUS triage study group has demonstrated that identifying low-risk chest pain patients by ambulance staff using a modified HEART score is feasible and safe when using a high-sensitive troponin T measurement in the hospital laboratory 22.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown the safety of identifying low-risk chest pain patients in a prehospital environment 22 23. The FAMOUS triage study group has demonstrated that identifying low-risk chest pain patients by ambulance staff using a modified HEART score is feasible and safe when using a high-sensitive troponin T measurement in the hospital laboratory 22.…”
Section: Discussionmentioning
confidence: 99%
“…They have also shown that using a POC troponin T measurement to turn the HEAR score into the HEART score in the prehospital setting has important additional predictive value 31. Furthermore, they have shown that in patients suspected of NSTE-ACS, HEART score assessment using a POC troponin T measurement by ambulance paramedics is accurate in identifying low-risk patients 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was the occurrence of major adverse cardiac events within 30 days. 26 In addition, van Dongen, et al 27,28 have evaluated both the HEART and HEAR scores in the prehospital setting. The primary outcome for both papers was major adverse cardiac events within 35 days.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 Due to limited diagnostic tests, the AMI diagnosis is challenging in the prehospital emergency setting, [3][4][5] and the value of prehospital risk stratification with point-ofcare troponins with or without risk assessment scores has received increased attention during the last decade. [6][7][8] Still, there is no prehospital strategy that safely excludes AMI outside of hospitals. 5 8 9 The introduction of high-sensitivity assays for cardiac troponins opened for rapid diagnostic pathways in hospitals, [10][11][12] and the diagnostic utility of the 2015 European Society of Cardiology (ESC) 0/1-hour algorithm for high-sensitivity cardiac troponin T (hs-cTnT) 2 has been confirmed in large validation studies from hospital emergency departments (EDs).…”
Section: Introductionmentioning
confidence: 99%